2003
DOI: 10.1177/0539018403042002001
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital: Recent Debates and Research Trends

Abstract: The aim of this article is not only to provide an overview of the state of recent discussion about the concept of social capital, it is also an attempt at critical reflection on theoretical and empirical research efforts. The question is whether the concept of social capital is a fashionable (and short-lived) term proposed as a cure-all for the maladies affecting contemporary communities, organizations and societies as a whole or whether it has more long-term strategic - theoretical as well as applicable - mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(110 citation statements)
references
References 17 publications
1
102
0
7
Order By: Relevance
“…By examining two specific concepts of CSR, it is undoubtedly true that CSR positively affects both perceived value of sustainability [37,73] and C-C identification [10,[12][13][14]38]. Moreover, this study confirmed the importance of social capital, as in [74][75][76]. The results obtained from this study offer important contributions and have important implications for both marketing academia and practitioners.…”
Section: Contributionsupporting
confidence: 59%
“…By examining two specific concepts of CSR, it is undoubtedly true that CSR positively affects both perceived value of sustainability [37,73] and C-C identification [10,[12][13][14]38]. Moreover, this study confirmed the importance of social capital, as in [74][75][76]. The results obtained from this study offer important contributions and have important implications for both marketing academia and practitioners.…”
Section: Contributionsupporting
confidence: 59%
“…Satu ciri yang selalu melekat dalam konsep modal sosial adalah bahwa ia bukan entitas tunggal (it is not a single entity … dalam definisi Coleman, 1998: S98), tetapi entitas yang multi dimensi dan multi spektrum (Yustika, 2006: 200). Karena itu, tidak aneh bila sampai sekarang terdapat banyak ragam definisi tentang modal sosial, yang menjadi sumber perdebatan (misalnya: Adam & Roncevic, 2003;Addler & Kwon, 2002;Fine & Lapavitsas, 2004;Lin, 1999;Portes, 1998;Quibria, 2003;Robison et al, 2000). Keragaman definisi disebabkan ragam pendekatan, fokus, orientasi, dan konsep yang dijadikan acuan dalam berbagai kajian, seperti yang dihimpun Dasgupta & Serageldin (1999) Coleman (1988) dalam memfasilitasi pencapaian tujuan melalui pemanfaatan sumber daya secara kolektif diidentifikasi dan diformulasikan oleh Johnson et al, (2002), (Lihat Gambar 1).…”
Section: ): Such Dormancy Is Caused By a Lack Of Social Capital Sociunclassified
“…To date, there are at least four ways of looking at the social capital [5]. First, the communitarian view, which sees the number and density of a group within a community, considers social capital as something inherently good, and in view of its continued, communitarian view implicitly assuming that the community benefits [6]. Apart from some biased facts from this point of view, the communitarian approach can already portray some of the social structures that live in society.…”
Section: Introductionmentioning
confidence: 99%
“…In this view, social capital as a 'bond' because of the strength of relations within a community (intercommunity) can give every family and community a common purpose [6]. Furthermore, social capital as a 'bridge' is meaningless in the absence of weaknesses of intercommunity ties, such as social diversity triggered by differences in religion, class, entity, gender, and socioeconomic status [6]. Thus, the view of this network can be characterized in two key propositions: (i) social capital is a double-edged sword.…”
Section: Introductionmentioning
confidence: 99%